2017
DOI: 10.1097/bpb.0000000000000403
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of daytime and after-hours surgical treatment of supracondylar humeral fractures in children

Abstract: therapeutic study (retrospective comparative study), Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…There were studies that documented surgeries done afterhours carried higher morbidity and mortality. [3][4][5][6][7][8][9][10][11] Chacko et al 3 performed a retrospective study of 767 consecutive patients with intertrochanteric, subtrochanteric, or femoral neck fractures and found that the duration of surgery, blood loss, and postoperative mortalities were significantly less for surgery done during the day compared with night. Ricci et al 4 conducted a prospective study among 203 patients with femur and tibia fractures comparing surgeries done at daytime and after-hours.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There were studies that documented surgeries done afterhours carried higher morbidity and mortality. [3][4][5][6][7][8][9][10][11] Chacko et al 3 performed a retrospective study of 767 consecutive patients with intertrochanteric, subtrochanteric, or femoral neck fractures and found that the duration of surgery, blood loss, and postoperative mortalities were significantly less for surgery done during the day compared with night. Ricci et al 4 conducted a prospective study among 203 patients with femur and tibia fractures comparing surgeries done at daytime and after-hours.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that daytime surgery has the potential to reduce minor complication rates for intramedullary nail fixation. Aydogmus et al 5 found that among 91 patients with Gartland type 3 fractures, pediatric supracondylar humerus fractures, after-hours surgery resulted Journal of Orthopaedic Surgery 27 (2) in higher poor fixation rate compared with daytime surgery. Kelz et al 6 reported a retrospective study of 144,740 nonemergent general and vascular surgical procedures, comparing the operation start time of 7 a.m. to 4 p.m., 4 p.m. to 6 p.m., and 6 p.m. to 11 p.m. and found that morbidity was significant higher when the operation start time was later in the day.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations